Nanoscale electrostatic theory of epistructural fields at the water-protein interface - Fernandez, Ariel (2012)
Nanoscale solvent confinement at the protein-water interface promotes dipole orientations that are not aligned with the internal electrostatic field of a protein, yielding what we term epistructural polarization. To quantify this effect, an equation is derived from first principles relating epistructural polarization with the magnitude of local distortions in water coordination causative of interfacial tension. The equation defines a nanoscale electrostatic model of water and enables an estimation of protein denaturation free energies and the inference of hot spots for protein associations. The theoretical results are validated vis-à-vis calorimetric data, revealing the destabilizing effect of epistructural polarization and its molecular origin.